Impact of Socioeconomic Family and Student's Performance on Adolescent Sexual Knowledge Level - Muhammad Anas; Sopia Sapitri; Ninuk Dwi Ariningtyas; Uning Marlina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Lack of sexual education impacts high cases of sexual deviation. Early sex education is needed because there are many cases of sexual violence that attack children and adolescents. Parents play a vital role in sexual education, and it should be given directly by parents, especially mothers. This study aims to determine the relationship between the mother's education, parent's occupation, mother's religion, student's gender, age, education, and adolescent's sexual knowledge level in Manubar, Sandaran, East Kutai. Methods: Quantitative study using ordinal regression analysis method and cross-sectional study design. The instrument used was a sexual education questionnaire for adolescents. The research subjects were taken by the total sampling of students in grades 7-9 of junior high school and grades 10-12 of high school, totaling 98 students. Results: The validity and reliability test of all questionnaire items, Pearson correlation with significance less than 0.05 and Cronbach-alpha more than 0.8. Ordinal regression test with a significance of model fitting 0.700, Goodness of fit with a significance of 0.505. Pseudo-R-Square value, Nagelkerke Coefficient, 13.4%, shows the magnitude of the influence on adolescent sexual knowledge. Parameter estimated tests for the gender of students with a significance of 0.01, Odds Ratio of 0.312. Conclusion: Students' gender influences the level of adolescent sexual knowledge with the possibility of less category 1.88%, enough 70.22%, and good 27.90%. Abstrak: Latar Belakang: Kurangnya pendidikan seksual berdampak pada tingginya kasus penyimpangan seksual. Orang tua sangat berperan dalam proses pendidikan seksual dan sebaiknya diberikan langsung oleh orang tua terutama ibu. Penelitian untuk mengetahui hubungan sosioekonomi keluarga dan performan siswa terhadap pengetahuan seksual remaja di Kecamatan Sandaran Kabupaten Kutai Timur. Metode: Penelitian kuantitatif cross-sectional dengan analisis regresi ordinal menggunakan instrument kuesioner pendidikan seksual bagi remaja. Subyek penelitian diambil secara total sampling murid kelas 7-9 SMP dan kelas 10-12 SMA sejumlah 98 siswa. Hasil: Uji validitas dan reliabilitas semua item kuesioner, korelasi pearson dengan signifikansi kurang dari 0,05 dan Cronbach-alpa lebih dari 0,8. Uji regresi ordinal dengan signifikansi model fitting 0,700, Goodness of fit, Pearson Chi-Square, dengan signifikansi 0.505, mengindikasikan data yang dievaluasi reliabel dan berkerja dengan baik pada model. Nilai Pseudo-R-Square, Nagelkerke Coefficient, 13.4% menunjukkan besaran pengaruh pada pengetahuan seksual remaja. Uji parameter estimasi jenis kelamin siswa dengan signifikasi p= 0.01, Rasio Odd 0.312. Kesimpulan: Jenis kelamin siswa berpengaruh terhadap tingkat pengetahuan seksual remaja dengan kemungkinan kategori kurang 1,88 %, sedang 70,22%, dan baik 27,90%.